2007
DOI: 10.1007/s10800-007-9404-3
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of CoWP film II. Effect of electrolyte concentration

Abstract: CoWP films were electrodeposited on coppercoated silicon wafers from citrate electrolyte containing cobalt sulphate, sodium tungstate and sodium hypophosphite at room temperature potentiostatically. The effects of electrolyte concentration on thickness, composition and microstructure of the films were studied. It was observed that the deposition current density and thickness increased with increasing cobalt and hypophosphite ion concentrations, whereas an increase in tungstate ion concentration resulted in a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 29 publications
3
7
0
Order By: Relevance
“…1i) and so does their roughness under certain conditions with electrolyte temperature increasing to 60°C (i c = 5 A/dm 2 ) ( Table 2). The similar effect associated with increase in phosphorus content of the alloy is noted in [34].…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…1i) and so does their roughness under certain conditions with electrolyte temperature increasing to 60°C (i c = 5 A/dm 2 ) ( Table 2). The similar effect associated with increase in phosphorus content of the alloy is noted in [34].…”
Section: Resultssupporting
confidence: 73%
“…Increasing phosphorus content of Co-W-P alloy [34] decreases the sizes of crystallites. Figure 3 shows that the nanohardness of ternary alloys increases with loading.…”
Section: Resultsmentioning
confidence: 95%
“…Recently, it has been reported that electrodeposition method has some advantages over electroless deposition such as lower processing temperature, better control over the deposition technique and thus, a wide range of compositions [12][13][14][15]. In the present work, Co-W-P coatings have been made on plain carbon steel by the electrodeposition method and their microstructures, hardness and corrosion protective properties have been studied.…”
Section: Introductionmentioning
confidence: 96%
“…Co-W-P thin films can be fabricated by both electroless [8][9][10][11] and electrochemical deposition methods [12][13][14][15]. Recently, it has been reported that electrodeposition method has some advantages over electroless deposition such as lower processing temperature, better control over the deposition technique and thus, a wide range of compositions [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Co-W-P thin films can be deposited by both electroless [10][11][12] and electrochemical [17][18][19][20] deposition methods. The electroless plating, however, is widely used to deposit the metallic capping/barrier layers because it is a very simple and inexpensive method, does not require much instrumentations and offers highly selective and conformal deposition [5,12,15].…”
Section: Introductionmentioning
confidence: 99%